2011
DOI: 10.1007/s11433-011-4367-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and magnetic properties of FeRh thin films with Pt doping

Abstract: In this paper, the structure and magnetic properties of FeRh alloy thin films with a small amount of Pt doping fabricated onto a glass substrate by sputtering are investigated systematically. XRD results show that the diffraction pattern of as-deposited film exhibits only nonmagnetic γ phase. After annealing, the disordered γ phase transforms to an ordered α′ phase. The temperature dependence of saturation magnetization of different annealing times and Pt contents are characterized. The phase transition temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In the M ( T ) data of Figure e, it can also be appreciated that at room temperature, in the AFM state, there is a residual magnetization (around 40 emu/cm 3 ), indicating the persistence of a residual FM phase. As expected, the residual magnetization is significantly smaller in the FeRh-SC film (≈14 emu/cm 3 ). Indeed, the FeRh film grown on the MgO-buffered tape is found to be more defective than that of the FeRh-SC film, as we shall confirm below.…”
Section: Resultssupporting
confidence: 81%
“…In the M ( T ) data of Figure e, it can also be appreciated that at room temperature, in the AFM state, there is a residual magnetization (around 40 emu/cm 3 ), indicating the persistence of a residual FM phase. As expected, the residual magnetization is significantly smaller in the FeRh-SC film (≈14 emu/cm 3 ). Indeed, the FeRh film grown on the MgO-buffered tape is found to be more defective than that of the FeRh-SC film, as we shall confirm below.…”
Section: Resultssupporting
confidence: 81%
“…28,29 This AFM-FM transition has been widely studied as well from a fundamental point of view. [30][31][32][33] The temperature at which the AFM order disappears (metamagnetic transition temperature, T*) can be tailored by the application of external magnetic fields, 34 changing composition/ doping, 35,36 electrochemical processes, 37 hydrostatic pressure 38 or biaxial strain imposed by the substrate. [39][40][41][42][43][44][45][46] The two latter effects are related to the change of the FeRh unit cell across the transition, being the unit cell parameter smaller in the low temperature AFM phase than in the high temperature FM phase.…”
Section: New Conceptsmentioning
confidence: 99%
“…FeRh alloy, crystallized in the CsCl structure (α′-FeRh), displays a reversible transition from an antiferromagnetic to a ferromagnetic state upon heating. , The transition, which occurs at about 75 °C for equiatomic FeRh alloy, can be tuned by either changing the stoichiometric ratio of the alloy or doping with other elements, among other strategies such as hydrostatic pressure, biaxial strain imposed by the substrate, and local techniques such as ion implantation , or indentation . It was found that by exploiting its antiferromagnetic anisotropic magnetoresistance, FeRh can be used as a memristor …”
Section: Introductionmentioning
confidence: 99%